The Galileo affair : a documentary history - Finocchiaro, Maurice A., 1942-; Galilei, Galileo, 1564-1642; Galilei, Galileo, 1564-1642 (University of California, 1989)
"A classic introduction to Galileo's masterpiece."--William A. Wallace, author of Galileo's Logic of Discovery and Proof."-- Provided by publisher
Keywords: Galilei, Galileo, -- 1564-1642.; Galilei, Galileo, -- 1564-1642; Religion and science -- History.; Inquisition.; Religion et sciences -- Histoire.; TECHNOLOGY & ENGINEERING -- Mechanical.; SCIENCE -- General.; Inquisition; Religion and science; History